2021
DOI: 10.1101/2021.08.06.21261590
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age and smoking predict antibody titres at 3 months after the second dose of the BNT162b2 COVID-19 vaccine

Abstract: ObjectiveWe aimed to determine antibody (Ab) titres 3 months after the second dose of the BNT162b2 coronavirus disease-2019 (COVID-19) vaccine and to explore clinical variables predicting these titres in Japan.MethodsWe enrolled 378 healthcare workers (255 women, 123 men) whose blood samples were collected 91±15 days after the second of two inoculations of the BNT162b2 COVID-19 mRNA vaccine (Pfizer/BioNTech) given 3 weeks apart. Medical histories and demographic characteristics were recorded using a structured… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 24 publications
3
14
1
Order By: Relevance
“…Other study showed the smokers were at risk of a reduced immune response to COVID-19 vaccines, although more research is needed before firm conclusions can be drawn. 26 Our data shows that IgG titer response to SARS-CoV-2 antigen is generated both in systemic or mucosal compartments following the second dose of vaccine regimen. The antibody response against SARS-CoV-2 involves production of high concentrations of specific IgG in systemic circulation that then migrate to other mucosal sites but are detectable in very low amounts in saliva and other sites, even though the level of total IgA is high.…”
Section: Discussionmentioning
confidence: 64%
“…Other study showed the smokers were at risk of a reduced immune response to COVID-19 vaccines, although more research is needed before firm conclusions can be drawn. 26 Our data shows that IgG titer response to SARS-CoV-2 antigen is generated both in systemic or mucosal compartments following the second dose of vaccine regimen. The antibody response against SARS-CoV-2 involves production of high concentrations of specific IgG in systemic circulation that then migrate to other mucosal sites but are detectable in very low amounts in saliva and other sites, even though the level of total IgA is high.…”
Section: Discussionmentioning
confidence: 64%
“…However, the factors associated with a low antibody response to SARS-CoV-2 mRNA vaccines are not well understood. Smokers, patients with cancer and hematological malignancies, and organ transplant recipients have been reported to have a lower SARS-CoV-2 anti-spike antibody response than individuals without these characteristics after receiving SARS-CoV-2 vaccines (22)(23)(24)(25)(26). It is intriguing that the suboptimal responders in this study who did not produce adequate antibodies against measles or mumps produced adequate SARS-CoV-2 anti-spike antibodies after receiving the BNT162b2 vaccine.…”
Section: Muik Et Al (19) Measured the Neutralization Efficacy Of Sera...mentioning
confidence: 71%
“…To summarize, several studies reporting cases of cardiovascular side effects secondary to mRNA COVID-19 vaccines have been discussed. These include myocarditis, perimyocarditis, pericarditis, MIs, and Takotsubo syndrome [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] . Most pertinently, the time between vaccination and the onset of symptoms varied between complications.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, patients with comorbidities, specifically hypertension and active smoking, exhibited significantly lower antibody titers following COVID-19 vaccination, which could contribute to an increased likelihood of post-vaccine complications [22] . Another study sheds further light by promoting smoking cessation prior to vaccination to ameliorate the efficacy of the BioNTech Pfizer vaccine [23] .…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation